ANALISIS SISTEM PENGANGGARAN SERTA PENGARUHNYA TERHADAP KINERJA KEUANGAN YAYASAN AS-SYIFA (Studi Kasus Pada Yayasan As-Syifa Al-Khoeriyah) - Hakip, Dian (Program Studi Pendidikan Manajemen Perkantoran, 2012)
Watchfulness aim that want achieved in this watchfulness (a) to detects and learn budgeting system infoundation assyifa al-khoeriyah, (b) to detect and learn finance performance in foundation assyifa alkhoeriyah,(c) to detect and learn budgeting system influence towards finance performance achievementin foundation assyifa al-khoeriyah. In this research uses descriptive and verification forms and methodsof descriptive and explanatory survey. Data collection technique used was to analyze the financialreports as-Syifa foundation from 2005 until 2009. Methods of analysis and quantitative data usingdescriptive statistical analysis that uses path analysis (path analysis). The results of descriptive analysisshowed that the planning and management control in the foundation asyifa good enough. The resultof path analysis show the existence of linkages between the research variables, and the results of theestimated coefficients between variables influence the research can be determined that the planning andmanagement control have an influence on the financial performance of As-Syifa foundation.